The relevance of the metaphor of God as Father in a democratic, non-sexist and religious society: An African Christian perspective - Modise, Leepo; Wood, Hannelie (Stellenbosch Theological Journal, 2016)
This article consists of four parts. Firstly, the article indicates the impact of the ancient contextual factors of using Father as an attribute of God. The position and role of males and females in the ancient times is highlighted to give clear background why the human authors of the Scripture made use of the ‘father figure’ as the attribute of God. Secondly, attention is given to the revelation of Scripture that God has revealed God-self and how human writers encode the message to suit their context. Thirdly, the question of the relevancy of using God the Father as an attribute of God within a democratic, non-sexist society, and amidst complicated family lives, is addressed. Fourthly, recommendations are made on the multi-faceted attributes of God that can be used interchangeably within the given context. The article argues that God as Spirit is neither male nor female, but incorporeal, and therefore transcends all creation because God is the creator God and cannot be confined to any gender, colour or race.